High coercivity Sm2Fe17N3 submicron size powder prepared by polymerized-complex and reduction–diffusion process. (15th July 2016) - Hirayama, Y.; Panda, A.K.; Ohkubo, T.; Hono, K.
Abstract: High coercivity Sm2 Fe17 N3 submicron size powder was synthesized by the polymerized-complex (PC), hydrogen reduction (HR) and reduction–diffusion (RD) processes. A mixture of nano size SmO x, FeO x and SmFeO3 particles was first synthesized by the polymerized-complex method, which was then reduced to α-Fe and SmO x by hydrogen. Subsequent reduction diffusion using Ca metal led to the formation of submicron size Sm2 Fe17 powder with a mixture of CaO. After nitriding and rinsing, Sm2 Fe17 N3 powder with the average diameter of 0.69 ± 0.17 μm was obtained, which exhibited the coercivity of 2.32 T, the highest ever reported for ternary Sm2 Fe17 N3 anisotropic powder. Graphical abstract: